1987
DOI: 10.1073/pnas.84.20.7257
|View full text |Cite
|
Sign up to set email alerts
|

Pancreastatin and islet hormone release.

Abstract: The effect of pancreastatin on the release of insulin, glucagon, and somatostatin was studied in the isolated perfused rat pancreas. After an initial equilibration period (-20 to 0 min) with a basal glucose concentration (3.3 mM), the pancreata were perfused with either 16.7 mM glucose (040 min) or with 20 mM arginine (0-20 min). Pancreastatin was introduced 10 min prior to and throughout the administration of the high glucose and arginine and continued during their perfusion. As expected, the glucose and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 27 publications
4
60
1
Order By: Relevance
“…The potent effect of the C-terminal fragment of pancreastatin on pancreatic secretion suggested that this portion of the molecule is important for the biological activity [3] and that the Cterminal active fragments of pancreastatin may be generated in vivo at the site where it exhibits its physiological functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potent effect of the C-terminal fragment of pancreastatin on pancreatic secretion suggested that this portion of the molecule is important for the biological activity [3] and that the Cterminal active fragments of pancreastatin may be generated in vivo at the site where it exhibits its physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide has been shown to inhibit glucose-induced insulin release from the isolated perfused pancreas [3]. Porcine pancreastatin shows striking sequence similarity to a part of bovine chromogranin A [4 -81, a protein normally present in the secretory granules of endocrine and neuronal cells [9].…”
mentioning
confidence: 99%
“…Pancreastatin has been shown to inhibit endocrine and exocrine pancreatic secretions [2,3]. We recently found that rat pancreastatin inhibited pancreatic exocrine secretions produced by central vagal nerve stimulation [4], and suggested that pancreastatin acted by means of inhibiting vagal efferent nerve excitation.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] The role of PST as a regulatory enteropancreatic peptide has been established in the light of a variety of biologic effects in a number of tissues, which could be assigned to the carboxyl-terminal part of the molecule (see Sánchez-Margalet et al 15 for review). These effects are exerted on endocrine and exocrine pancreatic secretion, [16][17][18][19][20][21] gastric secretion, 22,23 parathormone release, 24 plasma catecholamine levels, 25 and memory retention. 26 Synthetic rat pancreastatin has also been shown to have biologic activity in various tissues.…”
mentioning
confidence: 99%